Indices of soil contamination by heavy metals – methodology of calculation for pollution assessment (minireview) - Weissmannová, Helena Doležalová; Pavlovský, Jiří (Environmental monitoring and assessment, 2017)
This article provides the assessment of heavy metal soil pollution with using the calculation of various pollution indices and contains also summarization of the sources of heavy metal soil pollution. Twenty described indices of the assessment of soil pollution consist of two groups: single indices and total complex indices of pollution or contamination with relevant classes of pollution. This minireview provides also the classification of pollution indices in terms of the complex assessment of soil quality. In addition, based on the comparison of metal concentrations in soil-selected sites of the world and used indices of pollution or contamination in soils, the concentration of heavy metal in contaminated soils varied widely, and pollution indices confirmed the significant contribution of soil pollution from anthropogenic activities mainly in urban and industrial areas.